Simulations of anion transport through OprP reveal the molecular basis for high affinity and selectivity for phosphate. - Pongprayoon, P; Beckstein, O; Wee, C; Sansom, MS (National Academy of Sciences, 2009)
The outer membrane protein OprP from Pseudomonas aeruginosa forms a phosphate selective pore. To understand the mechanism of phosphate permeation and selectivity, we used three simulation techniques [equilibrium molecular dynamics simulations, steered molecular dynamics, and calculation of a potential of mean force (PMF)]. The PMF for phosphate reveals a deep free energy well midway along the OprP channel. Two adjacent phosphate-binding sites (W1 and W2), each with a well depth of approximately 8 kT, are identified close to the L3 loop in the most constricted region of the pore. A dissociation constant for phosphate of 6 microM is computed from the PMF, within the range of reported experimental values. The transfer of phosphate between sites W1 and W2 is correlated with changes in conformation of the sidechain of K121, which serves as a "charged brush" to facilitate phosphate passage between the two subsites. OprP also binds chloride, but less strongly than phosphate, as calculated from a Cl(-) PMF. The difference in affinity and hence selectivity is due to the "Lys-cluster" motif, the positive charges of which interact strongly with a partially dehydrated phosphate ion but are shielded from a Cl(-) by the hydration shell of the smaller ion. Our simulations suggest that OprP does not conform to the conventional picture of a channel with relatively flat energy landscape for permeant ions, but rather resembles a membrane-inserted binding protein with a high specificity that allows access to a centrally located binding site from both the extracellular and the periplasmic spaces.